SOCIODRAMA LEARNING METHODS TO IMPROVE STUDENTS' SPEAKING SKILLS - I Nyoman Suparsa; Ida Bagus Nyoman Mantra (Bajang Institute, 2024)
This research is classroom action research, so the characteristics of this research are that it requires several steps in the form of a cycle. The subjects of this research were 6th-grade students at Elementary School 23 Denpasar, with the research object being that the sociodrama learning method can improve students' speaking skills. The observation and test methods were used, and the qualitative descriptive method was used when processing the data. Based on the research results, the student's average score was meager in speaking at the pre-cycle stage, namely 5.2. To increase students' average scores, in cycle 1, students are given guidance on speaking skills, and after that, their speaking abilities are assessed. What is assessed is (1) speaking fluency, (2) intonation, (3) appropriateness of topic, and (4) expression and facial expressions. However, the average value obtained was just more than adequate, namely 6.375. So, it is necessary to provide more guidance and assessment in cycle 2. In cycle 2, it has yet to be achieved, namely 7.3125 in the excellent category, because the expected average score is 8.8 in the particular category. Therefore, the research was continued in cycle 3. To improve the average score in cycle 2, in cycle 3, the things carried out in cycle two were repeated but with more emphasis on role-playing without a script which was rehearsed and evaluated several times without feeling nervous, embarrassed, or afraid. In cycle 3, a new average value that exceeds the expected average value 8.8, namely 8.90625 in the Special category, can be achieved.